A new look at low-energy nuclear reaction research - Krivit, Steven B; Marwan, Jan (Journal of environmental monitoring, 2009)
This paper presents a new look at low-energy nuclear reaction research, a field that has developed from one of the most controversial subjects in science, "cold fusion." Early in the history of this controversy, beginning in 1989, a strong polarity existed; many scientists fiercely defended the claim of new physical effects as well as a new process in which like-charged atomic nuclei overcome the Coulomb barrier at normal temperatures and pressures. Many other scientists considered the entire collection of physical observations-along with the hypothesis of a "cold fusion"--entirely a mistake. Twenty years later, some people who had dismissed the field in its entirety are considering the validity of at least some of the reported experimental phenomena. As well, some researchers in the field are wondering whether the underlying phenomena may be not a fusion process but a neutron capture/absorption process. In 2002, a related tabletop form of thermonuclear fusion was discovered in the field of acoustic inertial confinement fusion. We briefly review some of this work, as well.